Pembentukan Karakter Religius Siswa Melalui Peran Lingkungan Sekolah - Muhammad Nurul Huda Abdulloh; Umi Arifah (IAINU Kebumen, 2026)
Character education as a foundation for enhancing national dignity through a system of discipline and habits within the school environment. This research was conducted at MTS PSA Husnul Hidayah Karangtanjung, Kebumen, where students exhibited disrespectful behavior toward teachers, lacked discipline, frequently skipped school, dressed immodestly, and performed the five daily prayers less than perfectly. The research objectives were: 1) to determine the role of the school environment in shaping the religious character of students at MTS PSA Husnul Hidayah, and 2) to analyze factors influencing character formation at MTS PSA Husnul Hidayah. The research method used was qualitative, with data collection techniques including observation, interviews, and documentation. The first data analysis technique examined all data, examining, and analyzing it. The results showed that instilling religious character values ​​through the school environment. These values ​​include: worship values ​​(such as congregational Dhuha and Dzuhur prayers), ruhul jihad values ​​(the struggle against ignorance and laziness), moral values ​​(habituating 5S: Smile, Greet, Say Hello, Be Polite, Courteous), discipline values ​​(attendance, order, and enforcement of rules), and exemplary values ​​(the behavior of teachers and employees). Supporting factors include parental support, commitment of the school community, adequate facilities, and the Islamic boarding school environment. However, there are also inhibiting factors, namely the diverse backgrounds of students, lack of student awareness, and the influence of the social environment around the school.